Digitilising the integration of construction site information as a mean to reduce delay risks / Hanni Nur Hidayah binti Suria and Hafizah Mohd Latif - Suria, Hanni Nur Hidayah; Mohd Latif, Hafizah (2019)
Construction delays affect not only contractors, but also caused lost and waste to clients. The aim of this paper is to identify the problems related to delays and general idea of ways to reduce the risks. This research based on the design thinking approach and invloved two phases of studies, whereby data will be collected from different stakeholders involve in the construction stage. It is identified that if the daily progress of task can be traced and rescheduling can be done on that time, delay may be avoided. However, tradisional method of writing site daily in a physical log book is a tedious task that sometimes ignored at the constuction sites. Now with applicating the advance of technology like smart and mobile applicationss, the daily site dairy task can be done easily with flexibility of time and place. Thus, recording site dairy will be more efficient, in the same time reducing the risk of delay in construction process.